2010
DOI: 10.1080/07399331003725523
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence: Psychiatric Healing With Eye Movement Reprocessing and Desensitization

Abstract: Sexual violence, which affects one in three women worldwide, can result in significant psychiatric morbidity and suicide. Eye movement desensitization and reprocessing (EMDR) offers health care providers the option of a brief psychiatric intervention that can result in psychiatric healing in as few as four sessions. Because health care providers often hear stories of sexual violence from their patients, they are in an ideal position to make recommendations for treatment. The purpose of this article is to intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These are behaviours that are related to adverse life experiences in childhood, household dysfunction, bullying and humiliation. It has also been suggested that EMDR is useful for treating women who have experienced sexual violence (35). Mindfulness is inspired by Buddhism and based on the non-judgmental acceptance of somatic sensations, physical pain, thoughts, memories, or psychological distress.…”
Section: Eye Movement Desensitization and Reprocessing (Emdr)mentioning
confidence: 99%
“…These are behaviours that are related to adverse life experiences in childhood, household dysfunction, bullying and humiliation. It has also been suggested that EMDR is useful for treating women who have experienced sexual violence (35). Mindfulness is inspired by Buddhism and based on the non-judgmental acceptance of somatic sensations, physical pain, thoughts, memories, or psychological distress.…”
Section: Eye Movement Desensitization and Reprocessing (Emdr)mentioning
confidence: 99%
“…b) The Eye Movement Desensitization and Reprocessing Technique (EMDR): developed in the United States in the 80s by the psychologist Francine Shapiro, encourages reprocessing difficult and painful memories in different brain hemispheres [20].…”
Section: Emotional Changementioning
confidence: 99%